A descriptive study on coverage of hepatitis B vaccination among final year MBBS students in a private medical college, Bengaluru urban of India - S. A., Moahhmed Nihal; Devaru, S. Jagadish; P., Vrinda; Abhidhan, (International Journal of Research in Medical Sciences, 2025)
Background: Hepatitis B is one of the most common infections seen in all age and all around the world with high mortality and morbidity. Healthcare workers (HCW) are at risk of contracting the hepatitis B virus (HBV) from infected patients. Hence his study was conducted with an objective to study the coverage and factors affecting hepatitis B vaccination among medical students. Methods: The descriptive study was carried out among final year MBBS students of B. R. Ambedkar medical college, Bengaluru by adopting convenient sampling technique. A total of 72 students had given consent for the study. Results: Majority of the students 86% seem to have a good knowledge regarding hepatitis B and 97.2% have responded that it is necessary to get vaccinated. But on the other side only 33.3% students have been vaccinated with a minimum of single dose against hepatitis B. Top 3 reasons for not being vaccinated are lack of motivation, no need felt and never thought of vaccination. Conclusions: This study reveals that only 33.3% have been vaccinated with a minimum of single dose and 66.6% students are not vaccinated against hepatitis B. After the completion of analyses, the students were briefly educated on the necessity of vaccination, completion of course and the complications that could be avoided in future by volunteering to get vaccinated. Following this event, we saw the 91.7% of students who are motivated or have changed their perception towards vaccination. This shows the importance of health education and counselling.